2000
DOI: 10.1002/(sici)1521-186x(200005)21:4<272::aid-bem4>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Directed and enhanced neurite growth with pulsed magnetic field stimulation

Abstract: Pulsed magnetic field (PMF) stimulation was applied to mammalian neurons in vitro to influence axonal growth and to determine whether induced current would direct and enhance neurite growth in the direction of the current. Two coils were constructed from individual sheets of copper folded into a square coil. Each coil was placed in a separate water‐jacketed incubator. One was energized by a waveform generator driving a power amplifier, the other was not energized. Whole dorsal root ganglia (DRG) explant cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 40 publications
3
55
0
1
Order By: Relevance
“…Although changing magnetic force has been reported to increase the formation of neuronal processes (Blackman et al, 1993a;Macias et al, 2000) and enhance the release of neurotransmitters (DruckerColin et al, 1994), there were also contradictory evidences that sinusoidal magnetic force inhibits the production of neuronal processes (Blackman et al, 1993b;McFarlane et al, 2000). There is little information regarding the application of perpetual magnets to direct the orientation of neuronal processes during formation, although it has been known that neuronal processes can be directed by a pulsed magnetic field which generates electric currents (Macias et al, 2000). Our finding showed that simple magnets also direct the orientation of neural processes in cultured neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although changing magnetic force has been reported to increase the formation of neuronal processes (Blackman et al, 1993a;Macias et al, 2000) and enhance the release of neurotransmitters (DruckerColin et al, 1994), there were also contradictory evidences that sinusoidal magnetic force inhibits the production of neuronal processes (Blackman et al, 1993b;McFarlane et al, 2000). There is little information regarding the application of perpetual magnets to direct the orientation of neuronal processes during formation, although it has been known that neuronal processes can be directed by a pulsed magnetic field which generates electric currents (Macias et al, 2000). Our finding showed that simple magnets also direct the orientation of neural processes in cultured neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Electrical currents can generate magnetic force in the perpendicular direction, and they interact each others (Petridou et al, 2006;Schnabel and Struijk, 1999). Although the directions of neuronal processes have been known to be influenced by a pulsed magnetic field (Macias et al, 2000), it is still unknown whether static magnetic fields directly affect the neurite properties of neurons.…”
Section: Introductionmentioning
confidence: 99%
“…6,8,21,24,34,41,43,58,64 Most of these models allow the weight to drop onto an impounder resting on the exposed dura mater and provide a transducer between the weight mass and the impounder to record the dynamic parameters. The NYU device directly drops the mass onto the dura mater.…”
Section: Discussionmentioning
confidence: 99%
“…23,34 Specifically designed Helmholtz coils were used, 5 and a study using an animal model to investigate the bioeffects of PMF stimulation after acute SCI was designed. The histopathology, recovery of locomotor function, and changes in somatosensory-evoked potentials (SEPs) throughout the recovery period were evaluated.…”
mentioning
confidence: 99%
“…A substantial body of evidence has, over the last decade, demonstrated the influence of the electromagnetic fields on biological systems (Azanza and Moral 1996;Calvo and Azanza 1999;Cridland 1999;Morgado-Valle et al 1998;Macias et al 2000;Rosen 2003a, b). At present the mechanisms by which 50 Hz ELF magnetic fields interact at the cellular level is poorly documented.…”
Section: Introductionmentioning
confidence: 99%